Application guidelines of applying the “Sufficiency Economy Philosophy” in the operation of homestays in Chiang Rai province. - Khattiya, Suthada; Pomlukthong, Narong (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research focused on exploring the operation method and to classifieds management structure of homestays and also to investigate the application guidelines of applying the “Sufficiency Economy Philosophy” in the operation of homestays in Chiang Rai province, The main informant is a homestay in Chiang Rai that has been certified with 18 standards. Collect data from in-depth interviews. A phenomenological qualitative research study was conducted with the chairman of the community, leaders of community and homestay owners. The participants were selected by purposive sampling technique. In-depth interview was chosen as the main data collection technique. To enhance the quality intensity of the research the documentary research, business model canvas analysis exploratory factor analysis and content analysis were also conducted in this study. The finding indicated that to applying “Sufficiency Economy Philosophy” in the process of homestay in Chiang Rai province could be done by preserving formerly available resources. The entrepreneurs needed to maintain both natural resources and cultural resources by investing in the available resources in local place and not being extravagant investors. Philosophy of sufficiency economy emphasized on balancing the way of living. There are three principles which involved moderation, reasonableness, and self-immunity along with the conditions of morality and knowledge. The entrepreneurs should be run business prudently, honestly, and sedulous. Nonetheless, the assistance of the government towards stream knowledge gaining and knowledge of investment still crucial for the community because of these may need to spend amounts of money especially the investment on infrastructure and communication technology. Article history : Received 4 August 2018 Revised 24 December 2018 Accepted 26 December 2018 SIMILARITY INDEX = 1.25